Establishment of Rat Model of Drug-Induced Gingival Overgrowth Induced by Continuous Administration of Phenytoin - Yasuka Tamamori; Yukihiko Tamura; Tsuneyoshi Yamazaki; Keiichi Ohya (Elsevier, 2005)
It is well-known that the anticonvulsant drug, phenytoin (PHT), induces gingival overgrowth as a side effect. The mechanism of PHT-induced gingival overgrowth, however, is not well understood. One reason for this is the lack of an adequate animal model for the PHT-induced gingival overgrowth. The purpose of this study was to establish a rat model of the drug-induced gingival overgrowth. Fourteen-day-old rats were randomly divided into 3 groups (5 rats/group). The control rats received only the vehicle. The rats in the experimental group were injected with 50 mg/kg per day (group L) and 100 mg/kg per day (group H) of PHT. They received a subcutaneous injection of vehicle or PHT twice a day for 42 days. A charge-coupled device (CCD) laser displacement sensor was used for measurement of the severity of gingival overgrowth of the mandibles. There was no significant difference in the growth of rats between the PHT-injected and the control groups. The CCD laser displacement sensor can measure minute changes in the gingival overgrowth in rats, and a significant extension of the buccal gingiva was observed in groups L and H. Using the CCD sensor, it is possible to quantify the change in the gingiva under precise control of the PHT dose. Keywords:: side effect, gingival overgrowth, phenytoin, laser, animal model